Osnowa złej ziemi - Masłoń, Sławomir (Er(r)go. Teoria - Literatura - Kultura, 2012)
Sławomir Masłoń The Loom of the Land The essay endeavours to show that the problems encountered while attempting to determine the ontological status of The Manuscript Found in Saragossa (the original text does not exist; what is taken for it is a compilation of fragments in various languages) have a wider significance than merely a textological one. The way the fragments of the text reflect each other making the position of an interpreter very uncomfortable is reflected in the problems the main protagonist of the novel has with ascertaining the nature of reality he encounters in Sierra Morena, which is being constructed for him by means of multiple stories he is told during his journey and of which the novel mainly consists. Because these narrations cannot be classified as either cunning fictions or true renditions of reality, the status of the experience taking place becomes ever more problematic. Taking into account the structural impossibility of the all-encompassing perspective inscribed the novel, the essay tries to show that the status of the reality and the narratives presented in the text is very different from what is finally presented to the protagonist as the true interpretation of the events. Relying on “truths” whose origin is the discourse of the King and the Church, the interpretation attempts to “explain” the space which extends beyond such authority using categories which are not applicable to it. This space is also the space of narration as literary practice.